Identification and characterization of virulence-attenuated mutants in Ralstonia solanacearum as potential biocontrol agents against bacterial wilt of Pogostemon cablin. (October 2020) - Zhang, Yuyao; Li, Guangwei; Li, Qiao; He, Ling; Zhang, Yong; Wang, Yaqin; He, Hong
Abstract: Ralstonia solanacearum is a soil-borne pathogen that causes bacterial wilt worldwide. The virulence-attenuated mutants were able to combat the soil-borne plant diseases. In this study, we screened the virulence-attenuated mutant PRS-84-4-49 of Ralstonia solanacearum and demonstrated that this strain showed a significant biocontrol effect against patchouli bacterial wilt. Three putative virulence-attenuated mutants obtained in our previous preliminary screen were individually tested for their pathogenicity to patchouli plants. Mutant PRS-84-4-49 showed significantly less virulence to patchouli plants than the other investigated mutants. The virulence-attenuated mutant PRS-84-4-49 was then evaluated for its potential to control patchouli bacterial wilt. The results revealed that the biocontrol treatment significantly reduced disease severity compared with the inoculated control plants, their highest disease incidence were 33% and 63%, respectively, at 5 days post-inoculation. Mutant PRS-84-4-49 exhibited less motility and produced fewer biofilms than the wild-type strain. Therefore, our results demonstrate that virulence-attenuated mutant of Ralstonia solanacearum has potential as biological control agent capable of suppressing patchouli bacterial wilt. Highlights: This work investigated the role of virulence-attenuated mutant PRS-84-4-49 of Ralstonia solanacearum in suppressing patchouli bacterial wilt. The Ralstonia solanacearum mutant exhibited less motility and produced fewer biofilms than the wild-type strain.